Bursting bubble in a viscoplastic medium. (10th September 2021) - Sanjay, Vatsal; Lohse, Detlef; Jalaal, Maziyar
Abstract: Abstract : When a rising bubble in a Newtonian liquid reaches the liquid–air interface, it can burst, leading to the formation of capillary waves and a jet on the surface. Here, we numerically study this phenomenon in a yield-stress fluid. We show how viscoplasticity controls the fate of these capillary waves and their interaction at the bottom of the cavity. Unlike Newtonian liquids, the free surface converges to a non-flat final equilibrium shape once the driving stresses inside the pool fall below the yield stress. Details of the dynamics, including flow energy budgets, are discussed. The work culminates in a regime map with four main regimes, all with different characteristic behaviours.